(untitled) (Research, Society and Development, 2021)
The Agreste Pernambucano Local Productive Clothing Arrangement (APLPCA) is responsible for 15% of the production of jeans in Brazil. However, the step of processing jeans in laundries, represents a significant contribution to the generation of negative environmental impacts in the region, which demonstrates the need for studies that identify and mitigate these impacts, ensuring the sustainability of the process. This exploratory and descriptive research approached the quantitative and qualitative perspective. For data collection, non-participatory observation, questionnaires and interviews were used, in order to carry out the classification, characterization and environmental diagnosis of laundries in the city of Caruaru - PE. It was observed that regarding the size, most of the laundries surveyed are micro (M) and small companies (P), considering the surveyed parameters: water consumption (M = 56%, P = 29%), useful area (M = 57 %, P = 39%), number of employees (M = 39%, P = 55%) and production (M = 40%, M = 52%). As for the potential polluter, it was found that most laundries (76%) perform dyeing, with potentially considerable polluter. It was found that all laundries do only the physical-chemical treatment of the effluents and that, within the parameters analyzed, none reached the desired efficiency, defined by environmental legislation. It is concluded that the jeans processing laundries have a high polluting potential, with negative environmental impacts due to the high water consumption and consequent generation of effluents. On the other hand, they generate positive environmental impacts, by generating jobs and income.